2003
DOI: 10.1109/tmc.2003.1255648
|View full text |Cite
|
Sign up to set email alerts
|

Geographic random forwarding (geraf) for ad hoc and sensor networks: multihop performance

Abstract: In this paper, we propose a novel forwarding technique based on geographical location of the nodes involved and random selection of the relaying node via contention among receivers. We focus on the multihop performance of such a solution, in terms of the average number of hops to reach a destination as a function of the distance and of the average number of available neighbors. An idealized scheme (in which the best relay node is always chosen) is discussed and its performance is evaluated by means of both sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
582
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 730 publications
(587 citation statements)
references
References 36 publications
4
582
0
1
Order By: Relevance
“…3, we report both the success probability curve P s (x) and Γ (x) as a function of the normalized distance x/R. Clearly, P s (x) drops as x → R and this is the reason for which the often considered [6,18] maximum advancement within radius metrics does not represent the optimal relay node selection criterion when fading is taken into account. It shall be observed that our derivation is an extension of previous results.…”
Section: Characterization Of Optimal Advancementsmentioning
confidence: 99%
See 4 more Smart Citations
“…3, we report both the success probability curve P s (x) and Γ (x) as a function of the normalized distance x/R. Clearly, P s (x) drops as x → R and this is the reason for which the often considered [6,18] maximum advancement within radius metrics does not represent the optimal relay node selection criterion when fading is taken into account. It shall be observed that our derivation is an extension of previous results.…”
Section: Characterization Of Optimal Advancementsmentioning
confidence: 99%
“…In this section, we report some preliminary performance results by comparing our new approach with the GeRaf scheme proposed in [6]. The GeRaf framework consists of an integrated practical MAC/routing scheme based on pure advancements: its capacity of approaching the maximum possible advancements toward the destination makes GeRaf a good candidate for our investigation.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 3 more Smart Citations